Revision of Sapindus sect. Sapindus (Sapindeae, Sapindoideae, Sapindaceae), including the description of three new species - Franck, Alan R. (Phytotaxa, 2024)
Sapindus (Sapindaceae) consists of 13–20 species of trees that are well known for their soap-making properties and the utility of their hard, spheroidal seeds for ornament or games. Section Sapindus has the most wide-ranging distribution within the genus, native to the Americas, Asia, Melanesia, and Polynesia. The number of species recognized in sect. Sapindus has ranged from only one species (S. saponaria) in several treatments to as many as seven species in Radlkofer’s monograph of the family. Undertaking a revision of Sapindus sect. Sapindus, over 1000 herbarium specimens were studied (physically or digitally) and four species were studied in in the field and/or in cultivation. Within sect. Sapindus, 12 species are here recognized, including three newly described species (S. marikuru, S. motu-koita, and S. standleyi), one new combination (S. tricarpus), one new subspecies (S. saponaria subsp. jardinianus), and one new variety (S. drummondii var. glabratus). Oceanic and animal-mediated dispersal are likely responsible for the wide distribution of sect. Sapindus, and human-aided dispersal is probably much more limited than has been suggested by prior authors. The native distribution of S. saponaria subsp. saponaria is emended to include only southern Florida (USA), Mexico, the Caribbean Islands, Central America, South America, and the Galápagos. Another two species of Sapindus from Vietnam that cannot confidently be assigned to any one section of Sapindus are briefly discussed.